Kol Nidre Studies in the Development of Rabbinic Votive Institutions - Benovitz, Moshe (Brown Judaic Studies, 2020)
This book is an introduction to the laws of oaths and vows of various types as they appear in biblical, Second Temple, and rabbinic sources. These institutions developed over time, and the oaths and vows mentioned in Second Temple literature should not be understood in light of subsequent rabbinic development. On the contrary: it is precisely the Second Temple texts, however obscure they may be, that provide the clues toward understanding the evolution of these institutions in rabbinic literature.